Development of Digital Flipbook Media to Improve Students' Understanding of Social Studies Subjects Grade 5 Madrasah Ibtidaiyah: Pengembangan Media Flipbook Digital untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPS Kelas 5 Madrasah Ibtidaiyah - Arrum, Alfiatur Rohmah; Nurdyansyah, Nurdyansyah (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study is to analyze the effectiveness of the development of digital flipbook learning media to improve student understanding of social studies subjects for class V at MI Muhammadiyah 04 Moropelang. This study uses the type of R&D research with the ADDIE model. using data collection techniques, namely: Questionnaires or questionnaires, tests, and documentation. Meanwhile, the data analysis technique used percentage quantitative analysis technique, and paired T-test analysis. The results showed that in the digital flipbook media media for the distribution of flora and fauna in Indonesia, 90% of media experts, 85% of linguists and 96% of material/content experts found the results so that the media could be said to be very feasible. While the results of the effectiveness show the probability of sig. (2-tailed) of 0.000. So <0.05, it can be concluded that digital flipbook media material on the distribution of flora and fauna in Indonesia has an influence on increasing students' understanding.